2018
DOI: 10.3390/v10090495
|View full text |Cite
|
Sign up to set email alerts
|

Strategies to Encapsulate the Staphylococcus aureus Bacteriophage phiIPLA-RODI

Abstract: The antimicrobial properties of bacteriophages make them suitable food biopreservatives. However, such applications require the development of strategies that ensure stability of the phage particles during food processing. In this study, we assess the protective effect of encapsulation of the Staphylococcus aureus bacteriophage phiIPLA-RODI in three kinds of nanovesicles (niosomes, liposomes, and transfersomes). All these systems allowed the successful encapsulation of phage phiIPLA-RODI with an efficiency ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
22
1
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 35 publications
(29 citation statements)
references
References 50 publications
4
22
1
2
Order By: Relevance
“…and the membrane of transferosomes is supplemented with edge activators that allow vesicle deformability of the vesicle, allowing for high tissue permeability. All three vesicle types could be loaded efficiently with bacteriophages (10 7 PFU/mL), with encapsulation efficiencies ranging between 96.6 and 99.8% (Gonzalez-Menendez et al, 2018). Niosomes were found to protect best against low pH and high temperature environments, as it is believed that the non-ionic surfactants in niosomes are more stable in these conditions.…”
Section: Liposomal Encapsulationmentioning
confidence: 97%
See 1 more Smart Citation
“…and the membrane of transferosomes is supplemented with edge activators that allow vesicle deformability of the vesicle, allowing for high tissue permeability. All three vesicle types could be loaded efficiently with bacteriophages (10 7 PFU/mL), with encapsulation efficiencies ranging between 96.6 and 99.8% (Gonzalez-Menendez et al, 2018). Niosomes were found to protect best against low pH and high temperature environments, as it is believed that the non-ionic surfactants in niosomes are more stable in these conditions.…”
Section: Liposomal Encapsulationmentioning
confidence: 97%
“… Gonzalez-Menendez et al (2018) investigated the viability of encapsulating phages with liposomes and other carriers called niosomes and transferosomes. Briefly, the membrane of niosomes consists of non-ionic surfactants (e.g., Tween 20, Triton X-100, etc.)…”
Section: Implementation Of Biomaterials For Bacteriophage Deliverymentioning
confidence: 99%
“…However, González-Menéndez et al [60] showed that this technique does not always improve phage particle stability compared to storage of the naked phages. Some studies have also shown that phage encapsulation in nanovesicles can enhance stability by protecting the particles from environmental factors, although a study showed that this improvement was only noticeable during short-term but not during long-term storage [63].…”
Section: Desirable Traits In Phages With Antimicrobial Potentialmentioning
confidence: 99%
“…Nanocząstki te są pęcherzykami zbudowanymi z jednej, kilku lub kilkunastu przestrzeni wodnych oddzielonych od siebie zamkniętymi koncentrycznie dwuwarstwami lipidów naturalnych i/lub syntetycznych (32). Zakresy ich rozmiarów są zależne od rodzaju powstałych pęcherzyków i różnicują je na pęcherzyki wielowarstwowe (> 200 nm), duże pęcherzyki jednowarstwowe (100-400 nm) oraz małe jednowarstwowe pęcherzyki (< 100 nm) (18). W celu wyeliminowania możliwości wyłapywania liposomów przez komórki fagocytarne, dotarcia w większej ilości do komórek docelowych oraz zwiększenia efektywności działania, strukturę liposomów modyfikuje się poprzez dołączanie do ich powierzchni hydrofilowych grup karboksylowych lub polimerów (48).…”
Section: Mechanizmy Interakcji Fag-nanomateriałunclassified